Developing a craniomaxillofacial and cervical equipment module for surgeons in the austere environment: a systematic review. Issue 2 (February 2020) - Breeze, J.; Gibbons, A.J.; MacKenzie, N.; Combes, J.
Abstract: The treatment of craniomaxillofacial and cervical wounds in a disaster relief setting is done by clinicians from local medical treatment facilities, non-governmental organisations (NGO), or the military. Although each group and individual surgeon will need specific equipment, this will be restricted by weight, portability and interoperability. We systematically reviewed scientific and commercial publications according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The papers we identified described the portable equipment that is required to treat patients who need damage-control surgery (decompressive craniectomy, temporary stabilisation, and internal and external fixation of the facial bones) for craniomaxillofacial and cervical injuries in austere or military settings. Austere settings are those in which there is an inherent lack of infrastructure, such as facilities, roads, and power. A total of 35 papers or scientific articles recommended the equipment that is needed to manage these injuries, but we could find no module that was specifically designed for use in these environments. Multiple modules are currently required to provide comprehensive surgical care and many of the items in the existing maxillofacial and neurosurgical kits are rarely used, which increases the cost of initial procurement and resupply. Duplications in equipment between modules also increase the size, weight, and financial cost. We suggest the equipment that is required to make up a rationalised, lightweight, and compact module that can be used for all craniomaxillofacial and cervical operations in austere settings.